Chronic cold exposure enhances glucose oxidation in brown adipose tissue. (12th October 2020) - Wang, Zhichao; Ning, Tinglu; Song, Anying; Rutter, Jared; Wang, Qiong A; Jiang, Lei
Abstract: The cultured brown adipocytes can oxidize glucose in vitro, but it is still not fully clear whether brown adipose tissue (BAT) could completely oxidize glucose in vivo . Although positron emission tomography (PET) with 18 F‐fluorodeoxyglucose ( 18 F‐FDG) showed a high level of glucose uptake in the activated BAT, the non‐metabolizable 18 F‐FDG cannot fully demonstrate intracellular glucose metabolism. Through in vivo [U‐ 13 C]glucose tracing, here we show that chronic cold exposure dramatically activates glucose oxidation in BAT and the browning/beiging subcutaneous white adipose tissue (sWAT). Specifically, chronic cold exposure enhances glucose flux into the mitochondrial TCA cycle. Metabolic flux analysis models that β3‐adrenergic receptor (β3‐AR) agonist significantly enhances the flux of mitochondrial pyruvate uptake through mitochondrial pyruvate carrier (MPC) in the differentiated primary brown adipocytes. Furthermore, in vivo MPC inhibition blocks cold‐induced glucose oxidation and impairs body temperature maintenance in mice. Together, mitochondrial pyruvate uptake and oxidation serve an important energy source in the chronic cold exposure activated BAT and beige adipose tissue, which supports a role for glucose oxidation in brown fat thermogenesis. Synopsis: This study shows that mitochondrial pyruvate uptake and oxidation serves an important energy source in the chronic cold exposure activated BAT and beige adipose tissue, which supports a role for glucose oxidation in brown fat thermogenesis. Chronic cold exposure promotes glucose oxidation and enhances glucose flux into the mitochondrial TCA cycle in BAT and the browning/beiging subcutaneous white adipose tissue (sWAT). β3‐adrenergic receptor (β3‐AR) agonist enhances the flux of mitochondrial pyruvate uptake through mitochondrial pyruvate carrier (MPC) in the differentiated primary brown adipocytes. In vivo MPC inhibition blocks cold‐induced glucose oxidation, and impairs body temperature maintenance in mice. Abstract : This study shows that mitochondrial pyruvate uptake and oxidation serves an important energy source in the chronic cold exposure activated BAT and beige adipose tissue, which supports a role for glucose oxidation in brown fat thermogenesis.